HAMBATAN PELAYANAN KARTU HASIL STUDI (KHS) MAHASISWA - Jailani Jailani; Fakhruddin Fakhruddin (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2017)
The system of academic services based E-administration which should provide more optimal and timely, but in practice there are various obstacles and problems that impact on service delay of Card Study Results (KHS). KHS service delay is also affecting the access charging Study Plan Card (KRS) for the next semester. Moving and these problems, the researchers interested in conducting in-depth study of the inhibiting factors that affect service of Student’s Study Result Card (KHS). Design of the reaserch is a qualitative descriptive study by using field research (field research) located at the Faculty of Dakwah and communication UIN Ar-Raniry Banda Aceh. Data obtained based on observations and interviews with 6 informants consisting of Sub. Section Academic employees namely chief and his staff, and 40 students from four departments namely the Department of Communications and Broadcasting Islam, the Department of Guidance and Counseling Islam, the Department of Management Propagation and the Department of Community Development Islam, and 10 students consisting of 5 men and 5 women to each department. Results show the quality of service system based academic information e-administrassion existing Faculty of Dakwah and Communication UIN Ar-Raniry not sufficient, because the quality of service less effective as well as staff from the academic tends to slow in handle every student needs, other factors caused by moral responsibility of lecturers and expertise (skills) in the process of filling study results on faculty portal, as well as other supporting facilities such as electricity and internet network capacity.